2007
DOI: 10.1007/s10812-007-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

Spectral fluorescence and polarization characteristics of Z,Z-bilirubin IXα

Abstract: We have studied the spectral fluorescence and polarization characteristics of Z,Z-bilirubin IXα, at room temperature in chloroform and in aqueous buffer medium, within an equilibrium complex with human serum albumin (HSA), and also under low temperature conditions (T = -100 o C) in isobutyl alcohol. We have observed a bathochromic shift of the fluorescence spectra, which is most pronounced for the bilirubin-albumin complex. The following are considered as possible reasons for the observed dependence of the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Native bilirubin exhibits the complete green fluorescence as shown in Figure 3(A). The spectral fluorescence and polarization characteristics of Z,Zbilirubin IXα is well established (Plavskii et al, 2007). The native collagen exhibited a very weak fluorescence as shown in Figure 3 (B).…”
Section: Fluorescent Labelling and Confocal Microscopymentioning
confidence: 69%
“…Native bilirubin exhibits the complete green fluorescence as shown in Figure 3(A). The spectral fluorescence and polarization characteristics of Z,Zbilirubin IXα is well established (Plavskii et al, 2007). The native collagen exhibited a very weak fluorescence as shown in Figure 3 (B).…”
Section: Fluorescent Labelling and Confocal Microscopymentioning
confidence: 69%
“…E configuration). This configuration, now photobilirubin/lumirubin, allows for greater mobility of the pyrrole rings and subsequent emission behavior (38)(39)(40). Utilizing the property of bilirubin to fluoresce, aside from when bound to albumin, we found that the purified PPARa-LBD protein interacts with bilirubin and, when excited, has fluorescence (Fig.…”
Section: Bilirubin Selectively Binds Pparamentioning
confidence: 88%
“…Bilirubin, already recalled in the above "Bioluminescence" section as the fluorophore responsible for the yellow bioluminescence of cryptic eels, can be also a fluorescing biomarker in blood and bile [344]. In fact, bilirubin behaves as a bichromophore because of its molecular structure composed by two asymmetrical dipyrroles covalently linked by a methylene group [345]. This feature is responsible for exciton energy transfer events inside the chromophore, in turn affected by the molecule concentration, excitation wavelength and microenvironment, which can remarkably influence bilirubin absorption, fluorescence and quantum yield [346][347][348].…”
Section: Normal and Altered Cell And Tissuesmentioning
confidence: 99%